2013
DOI: 10.1136/bmjopen-2013-002988
|View full text |Cite
|
Sign up to set email alerts
|

Virtual colleagues, virtually colleagues—physicians’ use of Twitter: a population-based observational study

Abstract: ObjectiveTo investigate potential violations of patient confidentiality or other breaches of medical ethics committed by physicians and medical students active on the social networking site Twitter.DesignPopulation-based cross-sectional observational study.SettingThe social networking site Twitter (Swedish-speaking users, n=298819).PopulationPhysicians and medical students (Swedish-speaking users, n=237) active on the social networking site Twitter between July 2007 and March 2012.Main outcome measurePostings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 13 publications
0
25
4
Order By: Relevance
“…This report provides a clear summary of the current state of social media use in the pharmaceutical industry. We can find examples of cautionary statements [10] and of how we are learning to engage in this setting [11]. Considering research outside the industry, three speakers at ASCO 2014 addressed social media specifically.…”
Section: Listening Sharing and Engagingmentioning
confidence: 99%
“…This report provides a clear summary of the current state of social media use in the pharmaceutical industry. We can find examples of cautionary statements [10] and of how we are learning to engage in this setting [11]. Considering research outside the industry, three speakers at ASCO 2014 addressed social media specifically.…”
Section: Listening Sharing and Engagingmentioning
confidence: 99%
“…As a tool for education it can be both motivating and engaging to see how other units run things and allow good ideas to spread within our own teams. 5 The number of physicians using social media in a professional capacity is increasing, averaging 1 in 8 medically related tweets (13%). 5 A 2011 survey of physicians found that 24% of respondents used social media daily and 61% weekly to explore online medical information.…”
Section: Twittermentioning
confidence: 99%
“…5 The number of physicians using social media in a professional capacity is increasing, averaging 1 in 8 medically related tweets (13%). 5 A 2011 survey of physicians found that 24% of respondents used social media daily and 61% weekly to explore online medical information. 7 By selecting a medically and educationally focused list of people and organizations to follow on Twitter, one can quickly glean the most discussed topics and quickly and efficiently communicate and engage with their own team.…”
Section: Twittermentioning
confidence: 99%
See 2 more Smart Citations